Bone grafts: which is the ideal biomaterial?. (18th June 2019) - Haugen, Håvard Jostein; Lyngstadaas, Ståle Petter; Rossi, Filippo; Perale, Giuseppe
Abstract: Bovine xenograft materials, followed by synthetic biomaterials, which unfortunately still lack documented predictability and clinical performance, dominate the market for the cranio‐maxillofacial area. In Europe, new stringent regulations are expected to further limit the allograft market in the future. Aim: Within this narrative review, we discuss possible future biomaterials for bone replacement. Scientific Rationale for Study: Although the bone graft (BG) literature is overflooded, only a handful of new BG substitutes are clinically available. Laboratory studies tend to focus on advanced production methods and novel biomaterial features, which can be costly to produce. Practical Implications: In this review, we ask why such a limited number of BGs are clinically available when compared to extensive laboratory studies. We also discuss what features are needed for an ideal BG. Results: We have identified the key properties of current bone substitutes and have provided important information to guide clinical decision‐making and generate new perspectives on bone substitutes. Our results indicated that different mechanical and biological properties are needed despite each having a broad spectrum of variations. Conclusions: We foresee bone replacement composite materials with higher levels of bioactivity, providing an appropriate balance between bioabsorption and volume maintenance for achieving ideal bone remodelling.